2010
DOI: 10.2147/opth.s15521
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humor penetration of topical bimatoprost 0.01% and bimatoprost 0.03% in rabbits

Abstract: PurposeThe purpose of this study was to compare the aqueous humor concentrations of bimatoprost acid after topical instillation in rabbits of bimatoprost ophthalmic solution 0.01% and bimatoprost ophthalmic solution 0.03%, two commercially available intraocular pressure-lowering medications.MethodsMale Dutch Belted rabbits were divided into two treatment groups (four rabbits/eight eyes per group): bimatoprost 0.01% and bimatoprost 0.03%. Thirty microliters (μL) of study medication was to pically instilled into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
9
1
Order By: Relevance
“…In vitro studies have shown that BAC improves drug penetration through the corneal epithelial layer by making tight junctions more porous 21,41. However, in a recent preclinical pharmacokinetic study comparing bimatoprost 0.01% to bimatoprost 0.03% in rabbit eyes, no improvements in bimatoprost acid ocular penetration were observed with bimatoprost 0.01% levels 3.3- and −2.2-fold lower than bimatoprost 0.03% at 30 and 90 minutes, respectively, following topical administration (bimatoprost levels were not reported) 42. To date, no comparative clinical pharmacokinetic study has been reported with the two bimatoprost concentrations to clarify the role of increasing BAC in improving ocular distribution in healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies have shown that BAC improves drug penetration through the corneal epithelial layer by making tight junctions more porous 21,41. However, in a recent preclinical pharmacokinetic study comparing bimatoprost 0.01% to bimatoprost 0.03% in rabbit eyes, no improvements in bimatoprost acid ocular penetration were observed with bimatoprost 0.01% levels 3.3- and −2.2-fold lower than bimatoprost 0.03% at 30 and 90 minutes, respectively, following topical administration (bimatoprost levels were not reported) 42. To date, no comparative clinical pharmacokinetic study has been reported with the two bimatoprost concentrations to clarify the role of increasing BAC in improving ocular distribution in healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…Any ophthalmologist or patient concerns raised by the incomplete and potentially misleading conclusion published by Ogundele and Jasek1 can be addressed with a carefully constructed pharmacokinetic study with a complete time-concentration profile. We are currently preparing a manuscript that reports the findings of such a study design.…”
mentioning
confidence: 99%
“…We read with great interest the recent article by Ogundele and Jasek, 1 in which the authors concluded that bimatoprost ophthalmic solution 0.01% (Lumigan ® ; Allergan, Inc, Irvine, CA) produced lower bimatoprost acid concentration than bimatoprost ophthalmic solution 0.03% (Lumigan; Allergan, Inc) in the aqueous humor of rabbits. This conclusion was made based on two treatment time points (30 and 90 minutes) with a small sample size (n = 4) at each time point and with large variability.…”
mentioning
confidence: 99%
See 2 more Smart Citations